PENERAPAN PROBLEM BASED LEARNING BERBANTUAN MEDIA POWERPOINT UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN IPAS KELAS V SDN 106840 KAMPUNG BENAR - Fadiah; Umar Darwis; Nurjannah; Sukmawarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on observations, problems were identified during the learning process, including the continued use of lecture methods and the lack of use of instructional media. This resulted in a lack of student engagement. The research problem was formulated to determine teacher and student activities in enhancing student learning engagement through the application of PowerPoint-assisted Problem-Based Learning in fifth-grade science lessons. The purpose of this study was to determine whether the application of PowerPoint-assisted Problem-Based Learning can improve student engagement in fifth-grade science lessons at SD Negeri 106840 Kampung Benar. This study was a Classroom Action Research (CAR). The subjects were 26 fifth-grade students at SD Negeri 106840 Kampung Benar with a Minimum Completion Score (KKM) of 70. Data collection techniques included observation and tests, followed by analysis using simple statistical formulas. The results showed that teacher engagement was 89.47%. Student engagement was 92.10%. Student engagement was 88.46%. Based on the research data, it can be concluded that the implementation of PowerPoint-assisted Problem-Based Learning can improve student engagement in science in fifth-grade students at SD Negeri 106840 Kampung Benar.